University Teachers and Open Educational Resources: Case Studies from Latin America - Rodés, Virginia; Gewerc-Barujel, Adriana; Llamas-Nistal, Martín (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
The Open Education movement has made efforts to systematise experiences and to evaluate the adoption of Open Educational Resources (OER). However, OER adoption is not part of the prevailing paradigm in higher education, both at the global level and in Latin America. This paper describes results of a study that analysed the social representations regarding the development, use, and reuse of OER by university teachers in their pedagogical practices. We conducted a study of 12 cases from Latin American universities using data analysis based on Grounded Theory. The results show that the use and reuse of OER lacks of public and institutional policies. The main agents are teachers organised in teams that support OER adoption. The reasons that encourage the creation of OER are mainly intrinsic, such as the pleasure derived from contributing and sharing, as well as external and related to professional development needs from the reflection on one’s own educational practice. Educators consider it essential to evaluate the resources created so that they can be reused in continuous improvement processes. Commercial use and misappropriation of the works are two of the main tensions identified. The community factor of teaching guides most behaviours in OER adoption in educational institutions and is presented as an inherent part of the development and transformation of the curriculum.